The Effect of Plasma Electrolysis for Biodiesel Synthesis Using Waste Cooking Oil as a Raw Material and KOH Catalyst - Shoelarta, Shoerya; Saripudin; Fedianto, Rahmat Dani Dwi; Darojat , Moch Adli; Abdulloh, Sudrajat Harris; Hidayatulloh, Irwan; elizabeth, lidya (Department of Chemical Engineering, Politeknik Negeri Bandung, 2023)
The high consumption of cooking oil in Indonesia is directly proportional to the production of used cooking oil waste that can pollute the environment. To overcome this problem, used cooking oil is used as a biodiesel feedstock using the plasma electrolysis method. Plasma electrolysis is a synthesis process by applying a high voltage to the process. This study aims to determine the effect of the plasma electrolysis method with variations in voltage (400 - 500 volts) and the type of reagent (methanol and ethanol) on % yield and characteristics of biodiesel. The process is carried out by reacting used cooking oil with a reagent that is given a voltage until an electric discharge occurs and two layers are formed and the calculation of the specific energy requirements for the synthesis process is carried out. The results show that at a voltage of 500 volts with methanol reagent produces a yield of 85.73% with characteristics according to the SNI 7128:2015 standard such as density 888.36 Kg/m3, viscosity 5.79 Cst, acid number 0.39 mg - KOH/g, content ester 97.56% and flash point 117oC with the exception of water content 0.373%, with a specific energy requirement of 1758,031 J/mL.